The relationship of leadership styles towards employee’s motivation among employees at University Malaysia Perlis / Nur Azianty Azizan - Azizan, Nur Azianty (2014)
The purpose of this survey research is to explore the different types leadership styles in educational institutions which may affect employees motivation. The subjects of this study include 92 total officers and staffs in this organization. Data were collected and analyzed using the Statistic Package for Social Science (SPSS) version 18.0. The questionnaire distributed has three sections which Section A for Demographic Profile, Section B are about three categories of leadership styles chosen, and Section C for employees motivation questions. The employees will rate their leaders or managers according to the types of leadership styles. In addition, the employees motivation was affected based on how their leaders give direction and treat them in their workplace. According to the Section B, most of the employees rate their leaders as Transformational Leadership and Transactional Leadership. Moreover, based on Section C, the employees want to involve in decision making process and get more attention from the leaders.